KONTRIBUSI DAYA LEDAK OTOT LENGAN DAN BAHU TERHADAP HASIL PUKULAN GYAKU-TSUKI ATLET KARATE-DO DOJO RAPP KABUPATEN PELALAWAN - Intan Maysarah; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this research is that the attack that is launched does not get points and takes slow thrusts without explosive power, so that imposing a hit on the opponent does not penetrate the target because the opponent can dodge and react more quickly to the target. the athlete's punch. The purpose of this research was to determine the contribution of the explosive power of the arm and shoulder muscles to the results of the gyaku-tsuki attack of the RAPP karate-dojo athletes in Pelalawan Regency. The population in this study consisted of 14 RAPP karate athletes in Pelalawan Regency using total sampling technique. The tools in this research were the madicine ball pit and the gyaku-tsuki punch test. The data obtained was analyzed using the product moment correlation. Based on the analysis of the normality test, the data X gives a LoMax of 0.190 and an L table of 0.227, while variable Y gives a LoMax of 0.117 and an L table of 0.227. This means LoMax <Ltable. Based on statistical data analysis, the data is normally distributed. Based on the above analysis requirements test, the hypothesis test on variable X against variable Y data is 0.961> 0.684 Rhitung> R table data. Thus, there is a contribution of the explosive power of the arm and shoulder muscles with the results of the gyaku-tsuki stroke of karate-dojo athletes RAPP Pelalawan Regency contribution of 92.37%.Key Words: Arm and Shoulder Muscle Strength, Gyaku-Tsuki Punch